(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Biodiesel was produced from the transesterification of neem oil with methanol using alumina catalyst. The transesterification was carried out under the optimal condition of methanol to oil molar ratio of 6:1. The reaction for the production of biodiesel using alumina catalyst conforms to a pseudo – first order rate law with reaction rate constants of 0.0028, 0.0044, and 0.009 min-1 at 308, 318, and 328 K, respectively. Activation energy for the reaction was 48.45 kJmol-1 and pre – exponential factor (A) of 13.003. The thermodynamics parameters for the reaction was calculated as 46.02 kJmol-1 and -0.1449 kJmol-1 for enthalpy and entropy respectively. The Gibbs free energy was calculated to be 90.68, 92.13, and 93.58 kJ mol-1 at 308, 318, and 328 K, respectively. In this research, kinetics and thermodynamics study of biodiesel production from neem oil was carried out. This shows that kinetics study was carried out to determine the rate constants of the reaction, the reaction rate constants also increases concerning the temperature of the reaction. The thermodynamics study was carried out, the positive value of H, negative S and positive G indicate this reaction is endothermic and non – spontaneous.